2003
DOI: 10.1097/01.lab.0000063930.75913.b3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tubulin Beta II in Neural Stem/Progenitor Cells and Radial Fibers During Human Fetal Brain Development

Abstract: SUMMARY:Recent studies revealed that the "radial glia" in fetal rodent brains are dividing neuronal precursor cells. However, in fetal primate brains, this issue remains unclear, with previous reports indicating that radial glia are a specialized form of astroglia. To investigate the relationship between radial fibers (RFs) and neural stem/progenitor cells in the fetal human brain, we generated polyclonal antibodies to human nestin protein and developed a new mAb, KNY-379, by screening for antibodies that immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…In the microarray data, Retinol binding Protein 1 (RBP1, gene encoding the carrier protein for transport of vitamin A) which is necessary for growth and differentiation of epithelial tissues was 3.9-fold increased in fetal dermal skin cells and confirmation with RT-PCR at 6.45-fold higher expression. Others such as Tubulin beta 2B (up-regulated at 1.58) have been shown to be highly present in fetal brain development (Nakamura et al 2003). Other studies emphasize that wound healing is regulated by many cytokines, growth factors and their receptors (Constant et al, 1997;Peled et al, 2001;Werner and Grose, 2003;Yang et al, 2003) and it is suggested that efficient wound healing in fetal skin at early gestation is a result of the unique cytokine or growth factor profile.…”
Section: Discussionmentioning
confidence: 99%
“…In the microarray data, Retinol binding Protein 1 (RBP1, gene encoding the carrier protein for transport of vitamin A) which is necessary for growth and differentiation of epithelial tissues was 3.9-fold increased in fetal dermal skin cells and confirmation with RT-PCR at 6.45-fold higher expression. Others such as Tubulin beta 2B (up-regulated at 1.58) have been shown to be highly present in fetal brain development (Nakamura et al 2003). Other studies emphasize that wound healing is regulated by many cytokines, growth factors and their receptors (Constant et al, 1997;Peled et al, 2001;Werner and Grose, 2003;Yang et al, 2003) and it is suggested that efficient wound healing in fetal skin at early gestation is a result of the unique cytokine or growth factor profile.…”
Section: Discussionmentioning
confidence: 99%
“…Cells cultured for 4 days in DMEM/F12 medium with N2 supplement and fibronectin (differentiation medium) expressed neural cell-associated mRNA, TUB [31] , neurofilament middle chain (NFM) [32] and ␤ -catenin ( fig. 2 A) [33] .…”
Section: Induction Of Cloned Pax6-transfected Cellsmentioning
confidence: 99%
“…The differentiated cells were also fixed in PBS containing 4% PHA for 20 min at room temperature. Frozen sections of neurospheres were incubated with two primary antibodies to nestin (rabbit polyclonal; 1:500) 14 and D2-40 in PBS/0.1% Triton-X/10% normal goat serum at 41C overnight. Nuclei were stained with TO-PRO-3 s (Molecular Probes Inc., Eugene, OR, USA).…”
Section: Immunocytochemical Analysismentioning
confidence: 99%
“…Cell suspensions were grown using the neurosphere method 16 in a defined DMEM/F-12 (1:1)-based growth medium supplemented with human recombinant (hr-) epidermal growth factor (20 ng/ml, Invitrogen), hr-fibroblast growth factor 2 (20 ng/ml, PeproTech Inc, Rocky Hill, NJ, USA), hr-LIF(10ng/ml, Chemicon), heparin (5 mg/ml, Sigma, St Louis, MS, USA), B27 supplement (Invitrogen), 15 mM HEPES as previously reported. 14,16,17 To induce differentiation, neurospheres were plated on poly-ornithine-coated glass coverslips and cultured in the medium with all D2-40 in brain Y Nakamura et al three growth factors withdrawn and supplemented with 1% FBS. Cells were cultured for 14 days before fixation for immunocytochemistry.…”
Section: Human Neural Stem/progenitor Cells Culture and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation